2021
DOI: 10.1177/09622802211061635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of parametric and semi-parametric models with randomly right-censored data by weighted estimators: Two applications in colon cancer and hepatocellular carcinoma datasets

Abstract: In this study, parametric and semi-parametric regression models are examined for random right censorship. The components of the aforementioned regression models are estimated with weights based on Cox and Kaplan–Meier estimates, which are semi-parametric and nonparametric methods used in survival analysis, respectively. The Tobit based on weights obtained from a Cox regression is handled as a parametric model instead of other parametric models requiring distribution assumptions such as exponential, Weibull, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Although Weibull model has been applied to survival analysis for the patient with lung cancer study [ 31 ] and gastric cancer [ 32 ], to the best of our knowledge, this is the first time to apply Weibull parametric model with MRI radiomic features for survival analysis for the patients with EC. Using colon cancer patient data, a previous study [ 33 ] compared semi-parametric methods with parametric models based on Monte Carlo simulations study, even though semi-parametric models performed slightly better than the parametric approach, parametric models were superior to the semi-parametric model based on large dataset. However, another study shows the parametric model is generally better than the semi-parametric model for the survival study in cancer study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Weibull model has been applied to survival analysis for the patient with lung cancer study [ 31 ] and gastric cancer [ 32 ], to the best of our knowledge, this is the first time to apply Weibull parametric model with MRI radiomic features for survival analysis for the patients with EC. Using colon cancer patient data, a previous study [ 33 ] compared semi-parametric methods with parametric models based on Monte Carlo simulations study, even though semi-parametric models performed slightly better than the parametric approach, parametric models were superior to the semi-parametric model based on large dataset. However, another study shows the parametric model is generally better than the semi-parametric model for the survival study in cancer study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although we included 491 cases in this study, the total number of patients with death is still small ( n = 95 in training dataset). Larger dataset will be helpful to improve Weibull model fitting, as previous study showed that parametric model is superior to semi-parametric model when dataset is large for the estimation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [ 6 ] also studied this dataset, comparing parametric and semiparametric models on right-censored data. However, their study focused on a semiparametric model with a univariate nonparametric component using the covariate age.…”
Section: Hepatocellular Carcinoma Data Examplementioning
confidence: 99%
“…There are several important studies on the estimation of model (1) under right-censored data, as given in (2), such as refs. [ 4 , 5 , 6 ], among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation